Distribution Network Reconfiguration Algorithms: A Comparative Study - Guo, Lingxu; Huang, Zhigang; Wang, Jing; Yu, Guangyao; Zhou, Yanzhen; Chong, Zhiqiang; Li, Zhenbin (International Conference on Electronics Technology (Online), 2022)
Distribution network reconfiguration is the main measure of distribution network optimization, its purpose is to determine the optimal topology of distribution network, is an effective measure to reduce network loss, its mathematical essence is a complex multi-objective nonlinear combinatorial optimization problem. This paper first introduces the methods of distribution network reconstruction, which are divided into three categories: heuristic algorithm, artificial intelligence algorithm and mathematical programming algorithm. It simply analyzes the advantages and disadvantages of three kinds of distribution network reconstruction algorithms, and then analyzes three commonly used distribution network reconstruction algorithms: switch opening and exchange (SOE),Mixed Integer second-order Cone Programming (MISOCP) based on DistFlow model and optimal matching loop flow method. Finally, IEEE33 nodes are used to test the effectiveness of three kinds of distribution network reconstruction methods. After comparative analysis of three kinds of distribution network reconstruction methods, it is concluded that SOE method is a more accurate and efficient method to solve the distribution network reconstruction problem.